The causes of regional variation in U.S. poverty: A cross-county analysis - Dan Rickman (European Regional Science Association (ERSA), 1998)
The persistence of poverty in the modern American economy, with rates of poverty is some areas approaching those of less industrialized nations, remains a central concern among policy makers. Therefore, this study uses U.S. county-level data to explore potential explanations for the observed regional variation in the rates of poverty. The use of counties allows examination of both rural and urban poverty, with rural poverty being a relatively unexplored topic. Factors considered include those that relate to both area economic performance and the demographic makeup of the area. Specific factors examined include: economic growth, immigration, domestic migration, industry restructuring, and spatial mismatch.
Keywords: 330